Outcomes after 90Yttrium‐ibritumomab tiuxetan‐BEAM in diffuse large B‐cell lymphoma: a meta‐analysis. (16th April 2014) - Auger‐Quittet, Sophie; Duny, Yohan; Daures, Jean‐Pierre; Quittet, Philipe
Abstract High‐dose chemotherapy followed by autologous stem cell transplantation (ASCT) is a standard therapy in patients with relapsed/refractory diffuse large B‐cell lymphoma (DLBCL) who are chemosensitive. The combination of carmustine, etoposide, cytarabine, and melphalan (BEAM) is commonly used as a conditioning regimen. The addition of yttrium‐90 (90Y)‐ibritumomab tiuxetan (Zevalin®) to BEAM (Z‐BEAM) is increasingly being used to improve outcomes and overcome refractory disease. We conducted a literature review and meta‐analysis in order to evaluate the clinical effects of Z‐BEAM followed by ASCT in patients with DLBCL. A literature search was conducted for randomized controlled trials and observational studies of Z‐BEAM as a conditioning regimen for ASCT in adult patients with DLBCL. Extracted data included baseline patient demographics, overall response (ORR), complete response (CR), overall survival (OS), progression‐free survival (PFS), nonrelapse mortality (NRM), median time to ANC and platelet engraftment, and rate of myelodysplastic syndrome. Mixed‐effects models were used to determine estimates. Ten studies (N = 328) were included in the meta‐analysis. The 2‐year OS and PFS were 84.5% (n = 328) and 67.2% (n = 285), respectively. Outcomes were superior in patients with nontransformed lymphoma. Posttransplant, ORR and CR rates were 72.6% and 68.5%, respectively. The NRM rate was 6.3% and the incidence rate of myelodysplastic syndrome was 2.5%. Two‐year OS was significantly associated with pretransplant ORR (P = 0.008, τ2 = 0). There was no significant association between PFS and pretransplant response. Z‐BEAM is safe and effective as a conditioning regimen in relapsed/refractory DLBCL.